2022
DOI: 10.1155/2022/2819688
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Algorithm Integrated Fuzzy AHP-VIKOR Approach for the Investigation of W-Cut Insert Heat Exchanger for Cooling of Dielectric Fluid Used in Ultra-High Voltage Transformer

Abstract: This study proposes a novel W-cut twisted tape to evaluate and enhance the effectiveness of novel grooved tube heat exchanger. The experimental investigations are carried out with W-cut inserts, which possess two main control factors, namely, twist tape ratio (y = 3.5 to 6.5) and width tape ratio (WR = 0.43 to 0.6). The investigation results prove that in all cases the energy transmission and friction factor of W-cut insert along with the first law and second law efficiency are considerably higher than the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…These values vary from 7000 m 3 /h to 22000 m 3 /h. Different works carried out in the research area (Frota, 2019;Frota, 2021a;Frota, 2021b) have confirmed that there is a difficulty in measuring the air outlet temperature, which ends up having a direct impact on the metrological reliability of the system and, consequently, on the flow calculation. From airflow, the correction was performed using the median of the calculated values, which allowed for obtaining a more homogeneous and representative heat exchanger efficiency curve of the physical nature of the problem (Frota, 2019).…”
Section: Alternative #5 A5mentioning
confidence: 99%
See 1 more Smart Citation
“…These values vary from 7000 m 3 /h to 22000 m 3 /h. Different works carried out in the research area (Frota, 2019;Frota, 2021a;Frota, 2021b) have confirmed that there is a difficulty in measuring the air outlet temperature, which ends up having a direct impact on the metrological reliability of the system and, consequently, on the flow calculation. From airflow, the correction was performed using the median of the calculated values, which allowed for obtaining a more homogeneous and representative heat exchanger efficiency curve of the physical nature of the problem (Frota, 2019).…”
Section: Alternative #5 A5mentioning
confidence: 99%
“…As a contribution of the research, the authors affirm that the variation of the input parameters generates changes in the performance parameters, such as the friction factor, the Nusselt number, and the thermo-hydraulic performance factor. In the same line of research initiated by Keklikcioglu et al (2022), in order to evaluate and improve the thermal effectiveness of a shell and tube heat exchanger, Gowri et al (2022) proposed a study modifying the geometry of the heat exchanger. To analyze the problem, they used a multi-objective genetic algorithm (GA) in addition to applying the FAHP-VIKOR hybrid multicriteria method.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%